PKM PERCEPATAN KEPEMILIKAN AKTA KELAHIRAN DALAM MENINGKATKAN KESADARAN ADMINISTRASI NEGARA - Ria Yusnita; Rendi Anggita; Purwanto Bayu Sugiharto; Atala Noval Setia Ramadhan; Jaka Wijaya Kusuma; Hamidah Hamidah (Jurnal Abdimas Bina Bangsa, 2022)
A birth certificate is a civil registration certificate resulting from recording the event of a person's birth, in another sense a birth certificate is a form of identity of every child who is an inseparable part of the civil and political rights of citizens. The right to identity is a form of state recognition of one's existence before the law. Birth Certificate is also very influential to be recognized by the State regarding a person's nationality. But unfortunately in Indonesia today there are still children whose identities are not or have not been recorded on the birth certificate, so that de jure their existence is considered non-existent by the state. This causes children to be born without their name, genealogy and nationality recorded and unprotected. With the undocumented identity of a child causing a higher risk of child exploitation, children can become victims of human trafficking, experience violence, or violate labor regulations and worldwide, Indonesia is one of the countries with poor birth registration coverage